On the measurement of running style - Daumer,Martin; Trost,Michael; Subkowski,Paul; Schneider,Andreas; Mrowca,Damian; Ding,Rui; Gao,Han; Walther,Markus; Lederer,Christian (PeerJ PrePrints, 2014)
The measurement of running style must be ecologically valid. The individual running style has an impact on the running performance as well as the running injury risk. In order to increase the performance and lower the injury risk, runners should be educated towards a healthy running style. But before advice can be made it is crucial to distinguish running styles from each other. Thus, it is interesting to detect and optimize the running style of individuals. The goal is to evaluate the possibility for a running style app using accelerometry data, which is able to track and display the user’s current running style by using accelerometry data, based on which advice can be given for a healthy and efficient running style with the help of gaming tools (meta product). To validate the approach, a gold standard with outdoor running acceleration data has to be created.
Keywords: running style; ecological valitiy; accelerometry